River morphology study in sungai lembing due to impact of sedimentations and floods - Nor Farahin, Muhammad Azman Shah (2016)
A study on river morphology was conducted at Sg. Lembing, Kuantan, Pahang. The major contribution to the depositional process in the river is sediment which is composed by granular materials that have variety size and type. Excess sediment could cause the river level increase that can cause changes of the river morphology. This study focused on changes of river morphology by determine the point of the river that has major changes, sediment grain sizes and types, rainfall data and factors influencing sediment transportation. Three sampling stations have been chosen based on analysing the river changes between in year 2010 to 2015 by using google earth software. Started from upstream Sg. Lembing (Station 1), mid-stream Sg. Lembing (Station 2) and downstream Sg. Lembing (Station 3). Sampling data are collected in two day which is on 16 March 2016 and 23 March 2016. Sample of sediment for every station were sieved to get the sediment grain size. Sediment particles in every station were classified based from United State Army Corps Engineer table (USACE). The data from Department of Irrigation and Drainage and weather station 3930012 Sg. Lembing PCC Mill is used for analysed rainfall pattern. The rainfall data is collected from year 2008 to 2015 to identify the effect of the rainfall to the sediment transportation. Overall, the finding of the study show that the most size of sediment at Sg. Lembing between 2.360mm to 0.425mm. The minimum and maximum total yearly data is 1443mm and 3775.5mm at 2008 and 2011 respectively.